How Walmart built sustainability into the supply chain - Huchzermeier, Arnd (Henry Stewart Talks, 2016)
The case study reviews how Walmart, the retailer, transformed its approach to sustainability by leveraging its relationships with suppliers, customers, and staff, and making sustainability a core element of their business strategy.